Romania : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2006)
This 2006 Article IV Consultation highlights that macroeconomic results for Romania were not as strong in 2005 compared with 2004 on account of both internal and external factors. Growth slowed to 4.1 percent in 2005, with agricultural output falling as a result of floods, and industrial output growth slowing owing in part to the abolition of global textile quotas. Mixed progress has been made on structural reforms. Large-scale privatization has been successful, the liberalization of the electricity and gas markets has continued, and the national reference price for heating has increased.